When Do Displaced Persons Return? Postwar Migration among Christians in Mount Lebanon. Issue 2 (22nd January 2020) - Camarena, Kara Ross; Hägerdal, Nils
Abstract: Under what conditions will forcibly displaced persons return to their original homes after wars end? We draw on theories of labor migration to show that even displaced persons who have positive feelings toward their original location may nevertheless choose to return as regular visitors rather than permanent residents unless the location offers attractive economic opportunities. Furthermore, we argue that violence can create negative emotions not only toward geographic locations of bloodshed but also against its perpetrators. After ethnic wars, the displaced may be unwilling to return to intermixed locations, exacerbating ethnic separation. We study postwar migration among Lebanese Christians displaced during the 1980s and identify economic conditions using exogenous price shocks for olive oil, a major local export. Among policy implications for economic reconstruction and transitional justice, our most important insight is that sometimes we should help the displaced in their new location rather than induce permanent return to their old homes.